2023
DOI: 10.1038/s41598-023-28681-2
|View full text |Cite
|
Sign up to set email alerts
|

Automatic COVID-19 severity assessment from HRV

Abstract: COVID-19 is known to be a cause of microvascular disease imputable to, for instance, the cytokine storm inflammatory response and the consequent blood coagulation. In this study, we propose a methodological approach for assessing the COVID-19 presence and severity based on Random Forest (RF) and Support Vector Machine (SVM) classifiers. Classifiers were applied to Heart Rate Variability (HRV) parameters extracted from photoplethysmographic (PPG) signals collected from healthy and COVID-19 affected subjects. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…following on from successful small-scale studies proving the efficacy of PPG lower frequency variability for specific clinical application areas, to then gather big data for global digital health and disease monitoring, e.g. autonomic nervous system by HRV linked features derived from PPG monitoring during a pandemic such as with Covid-19 (Aliani et al 2023 ).…”
Section: Ppg Low Frequency Variability and Autonomic Functionmentioning
confidence: 99%
“…following on from successful small-scale studies proving the efficacy of PPG lower frequency variability for specific clinical application areas, to then gather big data for global digital health and disease monitoring, e.g. autonomic nervous system by HRV linked features derived from PPG monitoring during a pandemic such as with Covid-19 (Aliani et al 2023 ).…”
Section: Ppg Low Frequency Variability and Autonomic Functionmentioning
confidence: 99%
“…The relationship between the different indexes of HRV and inflammatory markers has been widely studied, and a meta-analysis of 51 studies has demonstrated that HRV indexes are inversely related to the levels of the inflammatory markers [18]. Recent studies have associated reductions in HRV with COVID-19 [19][20][21][22][23][24].…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…Decreased HRV has been reported in every single chronic disease, including the AIDs. In addition, decreased HRV is seen in many acute conditions including COVID-19 infection and the long-COVID syndrome [331][332][333][334][335][336][337].…”
Section: Cardiovascular Dynamicsmentioning
confidence: 99%